Analisis Faktor-Faktor yang Menjelaskan Tingkat Kematian Akibat Bunuh Diri pada Negara-Negara di Benua Asia dan Eropa - Yekti Widyaningsih; Setjiadi, Nerissa Netanaya (LPPM Universitas Negeri Jakarta, 2023)
Many Indonesians still view mental health as a taboo subject and people with mental disorders are treated like a disgrace. As a result, they have difficulty getting the help they need and can end in suicide. The objects of research are countries in Asia and Europe. The purposes of this research are to analyze factors explaining death rate due to suicide and to work out the grouping results of Asian and European countries. The methods used are multiple linear regression, Ward’s method clustering, and Biplot mapping. Based on the analysis result, it is obtained that factors of having no religion, alcohol consumption, and psychiatrists’ availability have significant positive relationships with suicide rate. Factors of income and unemployment have significant negative relationships with suicide rate. Factor of education level has no significant effect with suicide rate. Two groups of countries are formed, namely group 1 consisting of 46 countries and group 2 consisting of 44 countries. Result of mapping based on the groups using the Biplot method is able explain 63,7% of data diversity. Group 1 is a group of countries that have a high unemployment rate and low values in: suicide rate, proportion of irreligious people, Gross Domestic Product (GDP) per capita, number of psychiatrists, and education level. Group 2 is a group of countries that have high values in: suicide rate, proportion of irreligious people, GDP per capita, number of psychiatrists, and education level while the unemployment rate is low.